The Use of Iliac Stem Prosthesis for Acetabular Defects following Resections for Periacetabular Tumors. (22nd October 2013) - De Paolis, Massimiliano; Biazzo, Alessio; Romagnoli, Carlo; Alì, Nikolin; Giannini, Sandro; Donati, Davide Maria
Abstract : Introduction . The management of pelvic tumors is a challenge for orthopaedic oncologists due to the complex anatomy of the pelvis and the need to have extensive exposure. Various reconstructive techniques have been proposed with poor functional results and a high percentage of complications. Our purpose is to determine the functional results and the rate of complications of iliac stem prosthesis for acetabular defects following resections for periacetabular tumors. Materials and Methods . Between 1999 and 2012, 45 patients underwent pelvic resections for periacetabular bone tumors followed by reconstruction with stem cup prosthesis. The most common diagnosis was CS (chondrosarcoma, 29 cases), followed by OS (osteosarcoma, 9 cases) and metastasis (3 cases). In 33 cases, this implant was associated with massive bone allografts. Minimum follow-up required to evaluate functional outcome was 2 years. We classified pelvic resections according to Enneking and Dunham's classification and we used MSTS (musculoskeletal tumor system) score to evaluate functional outcomes. Results and Discussion . Sixteen patients died of their disease, three were lost to follow-up, four are alive with disease, and twenty-two are alive with no evidence of disease. Fifteen patients had local recurrence. Sixteen patients had bone or lung metastasis. We have had 6 infections, 2 aseptic loosening, and 2 cases of hip dislocation. Iliac sovracetabular osteotomy was fused in all cases at 10 months from surgery. Functional results were good or excellent in 25 of 31 patients with long-term follow-up (77%), with a percentage similar to that reported in the literature. Conclusion . The use of iliac stem prosthesis is a simple reconstructive technique that reduces operative times and risk of infection. It allows having good results and low rate of complications, but it should be performed in selected cases and centres of reference.